What makes advocacy work? Stakeholders' voices and insights from prioritisation of maternal and child health programme in Nigeria - Benjamin Uzochukwu; Chioma Onyedinma; Chinyere Okeke; Obinna Onwujekwe; Ana Manzano; Bassey Ebenso; Enyi Etiaba; Nkoli Ezuma; Tolib Mirzoev (BMC, 2020)
Abstract Background The Nigerian government introduced and implemented a health programme to improve maternal and child health (MCH) called Subsidy Reinvestment and Empowerment programme for MCH (SURE-P/MCH). It ran from 2012 and ended abruptly in 2015 and was followed by increased advocacy for sustaining the MCH (antenatal, delivery, postnatal and immunization) services as a policy priority. Advocacy is important in allowing social voice, facilitating prioritization, and bringing different forces/actors together. Therefore, the study set out to understand how advocacy works - through understanding what effective advocacy implementation processes comprise and what mechanisms are triggered by which contexts to produce the intended outcomes. Methods The study used a Realist Evaluation design through a mixed quantitative and qualitative methods case study approach. The programme theory (PT) was developed from three substantive social theories (power politics, media influence communication theory, and the three-streams theory of agenda-setting), data and programme design documentation, and subsequently tested. We report information from 22 key informant interviews including national and State policy and law makers, policy implementers, CSOs, Development partners, NGOs, health professional groups, and media practitioners and review of relevant documents on advocacy events post-SURE-P. Results Key advocacy organizations and individuals including health professional groups, the media, civil society organizations, powerful individuals, and policymakers were involved in advocacy activities. The nature of their engagement included organizing workshops, symposiums, town hall meetings, individual meetings, press conferences, demonstrations, and engagements with media. Effective advocacy mechanism involved alliance brokering to increase influence, the media supporting and engaging in advocacy, and the use of champions, influencers, and spouses (Leadership and Elite Gendered Power Dynamics). The key contextual influences which determined the effectiveness of advocacy measures for MCH included the political cycle, availability of evidence on the issue, networking with powerful and interested champions, and alliance building in advocacy. All these enhanced the entrenchment of MCH on the political and financial agenda at the State and Federal levels. Conclusions Our result suggest that advocacy can be a useful tool to bring together different forces by allowing expression of voices and ensuring accountability of different actors including policymakers. In the context of poor health outcomes, interest from policymakers and politicians in MCH, combined with advocacy from key policy actors armed with evidence, can improve prioritization and sustained implementation of MCH services.